Effectiveness of information services with the SGD(Small Group Discusion) approach to improve students' learning independence - Ramadhan, Muhammad Fiqri; Harahap, Ade Chita Putri (Universitas Islam Negeri Raden Intan Lampung, 2025)
The purpose of this study was to see the effectiveness of information services with the SGD (Small Group Discussion) approach in improving students' learning independence. Learning independence is a way for individuals to improve ideas, emotions, strategies, and actions that are directed at achieving learning goals. The researcher used a quantitative approach with a pre-experimental research type, which applied a one group pretest posttest design. The population was all BKPI students with a total of 120 students, the sample obtained was 30 students who had low learning independence conditions. The sample selected in this study used non-probability sampling, especially with the purposive sampling technique. Data collection used a learning independence scale. The paired sample t-test is a data analysis technique used with the help of SPSS version 22, with a significance level of α = 0.05. Based on the data obtained, the sig value (2-tailed) was 0.000 <0.05. So it can be concluded that Ho is rejected and Ha is accepted, so information services are effective with the SGD (Small Group Discussion) approach to increasing students' learning independence.